Problem Solving Ability Of Students Mathematics In Problem Based Learning - Nurdiana Siregar (Universitas Negeri Makassar, 2017)
The objective of this study were to determine the increasing of students’ problem solving ability and self confidence after the implementation of problem based learning and to see the interaction between gender and learning to increas problem solving ability and students’ self confidence. The method kuantitaif with the design of this research was quasi-experimental with factorial design is 22. There were 73 students as the sample of this study containing 36 students in grade VIII-5 and 37 students in grade VIII-6. The instruments of this students were test of problem solving and self confidence scale. The data were analyzed by applying two way analysis of variance (ANOVA). The result showed that (1) The increasing of students’ problem solving ability taught by using problem based learning was higher than that taught by using conventional learning (2) There was no interaction between gender and learning with increasing of students’ problem solving ability.